Škodljivi organizmi in škodljivi dejavniki na sadikah gozdnega drevja v obdobju 1997-2018 - Smolnikar, Peter (Acta silvae et ligni, 2019)
Pests and diseases together with harmful abiotic factors present a serious problem for the production of healthy and vital forest tree seedlings. In order to examine the most important and most frequently occurring harmful abiotic and biotic factors, we analyzed the annual reports of health surveys from 18 forest nurseries in the period 1997-2018. The results revealed that the observed injuries were caused by pathogenic fungi in 68 % of cases, insects in 29 % of cases and abiotic factors in 1.1 % cases. Injuries occurred on 45 different tree and shrub genera, with Quercus sp. and Pinus sp. being the most frequently damaged (24.1 % and 17.5 %, respectively). Damage was frequently observed on leaves or needles (64.0 %). The most commonly reported diseases were powdery mildews (Erysiphe sp.). The greatest variability in the number of pests and diseases appeared on pines (Pinus sp.). Damage to planting stock usually occurred at low intensity (up to 10 %) but varied considerably during the period. The production of quality and healthy planting stock requires a holistic approach to seedling care.
Keywords: bolezen; damage; disease; drevesnica; harmful organism; mlada rastlina; nursery; planting stock; poškodovanost; sadika; seedling; semenka; Slovenia; Slovenija; škodljiv organizem; young plant